2019
DOI: 10.1049/mnl.2018.5595
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on viscosity and tribological characteristics of blends of vegetable oils with CuO nanoparticles as additive

Abstract: High biodegradability, renewability and low toxicity of vegetable oils make them excellent lubricating base oils. Coconut oil (CO) when used as a lubricant at metallic interfaces exhibits a low coefficient of friction but high wear rate compared to mineral oils, which limits its application as a commercial lubricant, whereas mustard oil (MO) exhibits better wear resistance. The main objective of this work is to obtain an optimal blend of MO and CO to be used as an environment-friendly base oil and to add an op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…39 Using thermo-gravimetric analysis, it was found that the OOT of the thermal degradation of CO, mustard oil (MO) and a blend of (50% MO + 50% CO) is (300, 334, 311°C), respectively, while that of mineral oil (SAE20W40) is 290°C. 99 The temperature at which the rice bran oil begins losing mass is increased from 220°C to 260°C and 275°C due to the addition of 0.25 wt% and 0.5 wt% CaO nanoparticle additives, respectively. This finding demonstrates that the thermal stability of rice bran oil increased by 18.2% and 25% with the addition of 0.25 wt% and 0.5 wt% CaO nanoparticles, respectively.…”
Section: Oxidation Stability Of Bio-lubricantsmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Using thermo-gravimetric analysis, it was found that the OOT of the thermal degradation of CO, mustard oil (MO) and a blend of (50% MO + 50% CO) is (300, 334, 311°C), respectively, while that of mineral oil (SAE20W40) is 290°C. 99 The temperature at which the rice bran oil begins losing mass is increased from 220°C to 260°C and 275°C due to the addition of 0.25 wt% and 0.5 wt% CaO nanoparticle additives, respectively. This finding demonstrates that the thermal stability of rice bran oil increased by 18.2% and 25% with the addition of 0.25 wt% and 0.5 wt% CaO nanoparticles, respectively.…”
Section: Oxidation Stability Of Bio-lubricantsmentioning
confidence: 99%
“…A brief comparison of sustainability and durability enhancements of bio-lubricants against oxidation and high temperature 39,99,114. …”
mentioning
confidence: 99%
“…Mineral oils are mostly used in the motor and engine applications, which are also obtained from the petroleum-based crude oil. The mineral oil is harmful to the environment which causes more toxicity and non-biodegradable [3]. The mineral oil lubricants have hydrocarbons which cause those effects and the natural lubricants are obtained from esters [4].…”
Section: Introductionmentioning
confidence: 99%
“…Taking this environmental concern into consideration, most research works are aimed towards biofluid and vegetable oil which are non-toxic in nature and are easily biodegradable. Vegetable oils have a better boiling point, good flash point, high viscosity index and higher lubrication properties which resulted in less consumption from misting [11][12][13]. Choi et al [14] reported that the oil-based NF exhibited better thermal conductivity and convective heat transfer coefficient but there were some problems associated with these NFs due to the formation of the hydrophobic coating layer on the powder surface.…”
Section: Introductionmentioning
confidence: 99%